Secret Key Generation Schemes for Physical Layer Security - Kumar, Megha S.; Ramanathan, R.; Jayakumar, M.; Yadav, Devendra Kumar (Defence Science Journal, 2021)
Physical layer security (PLS) has evolved to be a pivotal technique in ensuring secure wireless communication. This paper presents a comprehensive analysis of the recent developments in physical layer secret key generation (PLSKG). The principle, procedure, techniques and performance metricesare investigated for PLSKG between a pair of users (PSKG) and for a group of users (GSKG). In this paper, a detailed comparison of the various parameters and techniques employed in different stages of key generation such as, channel probing, quantisation, encoding, information reconciliation (IR) and privacy amplification (PA) are provided. Apart from this, a comparison of bit disagreement rate, bit generation rate and approximate entropy is also presented. The work identifies PSKG and GSKG schemes which are practically realizable and also provides a discussion on the test bed employed for realising various PLSKG schemes. Moreover, a discussion on the research challenges in the area of PLSKG is also provided for future research.